Butterfly fauna of Biratnagar, Nepal - Subba, Bharat Raj; Tumbahangfe, Jawan (Nepalese Journal of Biosciences, 2015)
A total 31 species of butterfly belonging to 26 genera under six families were reported from Biratnagar, Nepal. Specimens were collected during March to June in 2015.